Assessing The Impact of Fintech Innovations On The Financial Performance of Nigeria's Listed Deposit Money Banks: A 2024 Perspective - Abdullahi, Dr Hussaini; Umar, Lawal Umar (Journal of Accounting, Economics, and Business Education, 2025)
Abstract This study investigates the impact of financial technology (fintech) on the financial performance of Nigerian Deposit Money Banks (DMBs), utilizing panel data from 2012 to 2024. The analysis reveals that fintech services positively affect the performance of banks in both the short and long run. Specifically, a 1% increase in fintech adoption leads to a 0.1% improvement in long-term performance, while a 1% rise in deposits also boosts performance by 0.1%. In the short term, the effect of fintech is more pronounced, with a 1% increase in fintech services resulting in a 1.2% improvement in performance. However, rapid fintech growth, larger bank size, and higher capital adequacy ratios have a negative impact on long-term profitability, suggesting inefficiencies linked to high operational costs and insufficient infrastructure. Older banks exhibit higher profitability, benefiting from accumulated experience, while deposit growth adversely affects short-term profitability due to the costs associated with deposit mobilization and competitive interest rates. To enhance performance, the study recommends that banks focus on increasing deposits through competitive products and leverage fintech for improved convenience and financial inclusion. Policymakers should reassess capital adequacy ratios to ensure they are aligned with bank size, risk, and technological capacity, while encouraging efficiency over expansion. Sustainable fintech growth should be supported by infrastructure development, effective risk management, and incentives for technological investments, to optimize bank efficiency, reduce costs, and enhance customer service.